The Politics of Scarcity and Barriers to Effective Anti-Hunger Advocacy in Philadelphia. Issue 3 (2nd July 2020) - Scola, Becki; Brown, Keith
ABSTRACT: Philadelphia is the poorest, large city in the United States, with approximately 26% of the population living below the poverty line. Consequently, the city also has some of the highest rates of food insecurity across the nation. To address this need, Philadelphia has a robust anti-hunger community that fills the gap where government programs prove insufficient. Nevertheless, the anti-hunger community has been limited in its ability to effectively reduce the rate of food insecurity among Philadelphian households. Based on interviews with forty-two leaders of Philadelphia's anti-hunger community, we argue that the concept of "scarcity" best explains how community leaders are making decisions in Philadelphia. The lack of resources in the anti-hunger community means that community leaders must focus the majority of their attention on feeding the poor. We contend that this focus on providing food comes at the expense of time and energy that could be directed at political and structural changes that might reduce the number of people who are hungry in the first place. We identify two barriers that have impeded an efficient, coordinated effort to reduce food insecurity in Philadelphia: 1) time spent responding to the state political climate; and 2) competition for resources in a scarce environment.